The Types and Effectiveness of Mobile Health Applications Used in Improving Oral Cancer Knowledge: A Mixed Methods Systematic Review - Kehinde Kazeem Kanmodi; Afeez Abolarinwa Salami; Kamini Shah; Fatemeh Vida Zohoori; Lawrence Achilles Nnyanzi (Health Science Reports)
ABSTRACT Background and Aims The global burden of oral cancer (OC) is enormous. Mobile health applications have been found to play a promising role in cancer prevention; however, no known systematic review evidence exists on whether the use of mobile health applications is effective in increasing public knowledge of OC or not. Therefore, this systematic review aimed to synthesize evidence on the types and effectiveness of mobile health applications used for improving OC knowledge. Methods This study adopted a mixed methods systematic review design. The review methodology was informed by Joanna Brigg's Institute's PRISMA checklist and the AMSTAR‐2 guidelines. The literature used for this review were obtained through the search of multiple sources, including 12 electronic databases, web sources, and manual searching of the reference lists and citations of the included articles. Quality appraisal of the included articles was done using the Mixed Methods Appraisal Tool, after which relevant data were collected, synthesized, and configured. Results A total of three high‐quality articles, from two studies conducted in India, were included in this review. The studies investigated 574 participants, who are predominantly doctors and community members, on two Android‐based mobile health applications (M‐OncoED and Prayaas). Only Prayaas was found to significantly increase OC knowledge among its users (p < 0.05). Only M‐OncoED was found to significantly increase the practice of OC screening advice provision among a selected group of users. No other significant finding was reported on the effect of OC knowledge obtained from the use of these applications on clinical, behavioral, and epidemiological outcomes. Conclusion Mobile health application‐based education is a highly underutilised but very promising strategy that can be used to improve public knowledge of OC. This strategy needs to be adopted in public education programmes on OC.